Single-Phase Grid-Connected Inverter With Predictive Control Cost Function for Leakage Current Mitigation and FAS Model - Cesar Limones; Nimrod Vazquez; Ricardo Femat; Leonel Estrada; Jeziel Vazquez; Claudia Hernandez; Angel de Castro; Joaquin Vaquero (IEEE Open Journal of the Industrial Electronics Society)
Leakage current is one of the main issues for transformerless grid-connected photovoltaic inverters, and its reduction is a primary focus of various studies reported in the literature. This article proposes and validates a finite control set model predictive controller with a novel cost function to mitigate leakage current in a single-phase full-bridge (FB) grid-connected inverter with an LCL filter, making no modifications to the traditional FB topology and without adding any extra components. Furthermore, mathematical modeling is based on the fully actuated system model, allowing a reduction in the number of variables sensed during implementation, resulting in only grid current and voltage being measured.